Moral Analysis in the Videos of Dongeng Kita Channel and Its Relevance to Indonesian Learning - Sugeng Santoso; Ni Luh Putu Rastiti Era Agustini; Ade Asih Susiari Tantri (STAI Hubbulwathan Duri, 2021)
This research aims to analyze the moral values in folklore videos on the Dongeng Kita Youtube channel and analyze its relevance to Indonesian learning in schools. The approach of this research is qualitative research, with a descriptive type. There are six video samples taken from the Dongeng Kita channel. The moral analysis is conducted by observing the sample videos and describing it according to theory, while relevance analysis is done by reviewing the applicable learning syllabus. The research found that the videos contained moral values of respect for others, not being disobedient to parents, being honest, not being lazy, not being bad, not being greedy, keeping promises, and not cheating. Besides, moral values were found to have relevance in Indonesian learning for the grade VII of Junior High Schools because the moral values can support the use of the Dongeng Kita channel as a learning media that is linear with the learning competencies of the 2013 Curriculum, which aims to develop student moral. It is expected that Indonesian teachers in schools will take advantage of the Dongeng Kita channel as a learning media to make learning more enjoyable.